SURVEI SARANA DAN PRASARANA PENDIDIKAN JASMANI SEKOLAH MENENGAH PERTAMA DI KECAMATAN JOGOROGO - Tatag Yudha Dwi Anggara; Andy Widhiya Bayu Utomo; Kuncoro Darumoyo (JOURNAL RESPECS (Research Physical Education and Sports), 2022)
The purpose of this study was to determine the condition of physical education facilities and infrastructure in Junior High Schools in Jogorogo District for the 2021/2022 academic year. This research is a quantitative descriptive study, in this study it describes the state of physical education facilities and infrastructure in junior high schools in Jogorogo District, Ngawi Regency. The data was obtained from the process of the researcher's visit to all State Junior High Schools in the Jogorogo District, then with the help of the physical education teacher, the researcher saw directly and filled in the data on the observation sheets both in warehouses and other places according to the observation sheets that had been arranged. The results of the study are based on the number of facilities and infrastructure categorized as good with a percentage of 66.66%, based on their condition categorized as good with a percentage of 66.66%, and ownership status categorized as self-owned by 66.66%.